A Jordan Ombudsman Bureau with Enhanced Capacity - Cuvillier, Emmanuel; Almaroof, Salam (World Bank, Washington, DC, 2015)
The Ombudsman Bureau in Jordan was established in 2008. It was created to provide an avenue for redress by citizens for complaints against public sector bodies - part of the Government s drive to improve the public sector. Such a body is important in providing checks and balances in a government dominated by a strong executive branch. It also provides an alternative process of dispute resolution to filing cases in courts, thus relieving pressure on the court system and providing a means of redress that may prove more accessible than the courts for certain categories of disputes.